Evektivitas Konseling Kelompok Dengan Teknik Restrukturisasi Kognitif Untuk Meningkatkan Kepercayaan Diri Siswa Kelas VII smp Negeri 2 Umbulsari - Khoirul Munajah; Muhammad Fikri Fauzi; Faisol Hakim (Jurnal Ilmu Bimbingan dan Konseling, 2026)
Self-confidence is very important and must be possessed by students, because with self-confidence students become confident in their abilities, think more objectively and responsibly in doing something according to their abilities. This study aims to test the effectiveness of group counseling with cognitive restructuring techniques in increasing self-confidence in general, as well as its specific indicators which include self-confidence, objectivity, and responsibility of grade VII students at SMP Negeri 2 Umbulsari in the 2025/2026 Academic Year. The research method used is quantitative experiment with one-group pretest-posttest design. Sampling was carried out through purposive sampling technique which resulted in 8 students as research subjects. Data were collected using observation, questionnaires, and documentation methods. The data analysis technique applied was paired sample t-test assisted by SPSS 23.0 software. The results of the analysis are (1) Variable Y obtained a t-value of 5.351 and a sig. value of 0.001, (2) Sub-variable Y1 obtained a t-value of 3.930 and a sig. value of 0.001. 0.006, (3) Sub variable Y2 obtained a t-value of 4.217 and a sig. value of 0.004, (4) Sub variable Y3 obtained a t-value of 2.956 and a sig. value of 0.021. Based on the results of the statistical test, the significance value of all variables is less than 0.05 so that the Working Hypothesis (Ha) is accepted. Thus, it can be concluded that group counseling services with cognitive restructuring techniques are significantly effective in increasing self-confidence, self-confidence, objectivity, and responsibility of class VII students of SMP Negeri 2 Umbulsari in the 2025/2026 academic year.